TiO2 coated Si nanowire electrodes for electrochemical double layer capacitors in room temperature ionic liquid - Konstantinou,F; Shougee,A; Albrecht,T; Fobelets,K (Journal of Physics D: Applied Physics, 2017)
Three TiO2 deposition processes are used to coat the surface of Si nanowire array electrodes for electrochemical double layer capacitors in the room temperature ionic liquid [Bmim][NTF2]. The fabrication processes are based on wet chemistry only and temperature treatments are kept below 450°C. Successful TiO2 coatings are found to be those that are carried out at low pressure and with low TiO2 coverage to avoid nanowires breakage. The best TiO2 coated Si nanowire array electrode in [Bmim][NTF2] showed energy densities of 0.9 Whcenterdotkg-1 and power densities of 2.2 kWcenterdotkg-1 with a nanowire length of ~10 μm.